Study on tourist satisfaction in Liangshan prefecture, China - Cai Changyan; Lim, Fui Yee Beatrice (Faculty of Business, Economics and Accountancy, 2021)
Liangshan Prefecture, located in southwest China, makes use of its unique climate advantages and superior natural conditions to vigorously create a new four-in-one health industry pattern of "health care and living” committed to building an international health care tourism resort. This paper firstly constructs the index system of tourism satisfaction; secondly, conducts descriptive analysis, reliability test, validity test, factor analysis and regression analysis to further explore the influencing factors of tourist satisfaction. Finally, we put forward suggestions to improve tourism development of Liangshan Prefecture in China.